Tests for the correct insertion of earplugs in the ear canal performed with the use of a portable device - Emil Kozłowski; Rafał Młyński (Nofer Institute of Occupational Medicine, 2021)
Background The aim of the study was to assess the correct insertion of earplugs in the ear canal by people with different knowledge regarding this matter. The use of hearing protectors leads to a reduction in the risk of hearing loss, which is part of environmental engineering. Material and Methods Measurements of sound attenuation by earplugs were carried out with the participation of 21 people with no experience in the use of earplugs. The measurements were repeated until the subjects had read the instructions for the use of earplugs, and then after the subjects had been trained in the correct insertion of earplugs in the ear canal. The tests were carried out using a newly developed portable device for quick measurements of sound attenuation. Results Familiarizing the subjects with the instructions for use resulted in a sound attenuation value being 6.7 and 3.3 dB higher, at 250 and 4000 Hz, respectively, compared to the measurement when the subjects inserted earplugs in the ear canal without any guidance. An even greater increase in attenuation was observed when the subjects were trained to insert earplugs, at 9.2 dB (250 Hz) and 5.4 dB (4000 Hz), respectively. In most cases, the changes in attenuation as a result of providing guidance were statistically significant. Conclusions Persons who have no experience in using earplugs have significant problems with their correct insertion. Reading the instructions for use does not guarantee that earplugs will be inserted correctly. Only the training showing how to insert the earplugs correctly results in people being able to do it correctly in most cases. Med Pr. 2021;72(5):521-8